20-HETE Enzymes and Receptors in the Neurovascular Unit: Implications in Cerebrovascular Disease - Gonzalez-Fernandez, Ezekiel; Staursky, Daniel; Lucas, Kathryn; Nguyen, Bond V.; Li, Man; Liu, Yedan; Washington, Chad; Coolen, Lique M.; Fan, Fan; Roman, Richard J. (Frontiers in Neurology, 2020)
20-HETE is a potent vasoconstrictor that is implicated in the regulation of blood pressure, cerebral blood flow and neuronal death following ischemia. Numerous human genetic studies have shown that inactivating variants in the cytochrome P450 enzymes that produce 20-HETE are associated with hypertension, stroke and cerebrovascular disease. However, little is known about the expression and cellular distribution of the cytochrome P450A enzymes (CYP4A) that produce 20-HETE or the newly discovered 20-HETE receptor (GPR75) in the brain. The present study examined the cell types and regions in the rat forebrain that express CYP4A and GPR75. Brain tissue slices from Sprague Dawley (SD), Dahl Salt-Sensitive (SS) and CYP4A1 transgenic rat strains, as well as cultured human cerebral pericytes and cerebral vascular smooth muscle cells, were analyzed by fluorescent immunostaining. Tissue homogenates from these strains and cultured cells were examined by Western blot. In the cerebral vasculature, CYP4A and GPR75 were expressed in endothelial cells, vascular smooth muscle cells and the glial limiting membrane of pial arteries and penetrating arterioles but not in the endothelium of capillaries. CYP4A, but not GPR75, was expressed in astrocytes. CYP4A and GPR75 were both expressed in a subpopulation of pericytes on capillaries. The diameters of capillaries were significantly decreased at the sites of first and second-order pericytes that expressed CYP4A. Capillary diameters were unaffected at the sites of other pericytes that did not express CYP4A. These findings implicate 20-HETE as a paracrine mediator in various components of the neurovascular unit and are consistent with 20-HETE’s emerging role in the regulation of cerebral blood flow, blood-brain barrier integrity, the pathogenesis of stroke and the vascular contributions to cognitive impairment and dementia. Moreover, this study highlights GPR75 as a potential therapeutic target for the treatment of these devastating conditions.